The Pattern of Budget Slack in Sharia Microfinance Institutions: A Phenomenology Study - Solihah, Solihah; Rohma, Frida Fanani (SAN Scientific, 2024)
This study explores budgetary slack in Islamic ultra microfinance institutions, specifically examining the role of religious affiliation. Using a qualitative phenomenological approach, data was collected through interviews at an Islamic Savings and Loans Financing Cooperative. The findings reveal a disparity between theoretical and practical perspectives on budgetary slack. An imbalance between targets and compensation drives actors to rationalize budgetary slack, exacerbated by information asymmetry. Religious affiliation primarily impacts business products and services but has little effect on subordinate behavior. Contrary to assumptions that budgetary slack is unlikely in Sharia-compliant systems, this study suggests that the Sharia institutional environment may still foster budgetary slack due to opportunistic behavior. This research is among the first to examine budgetary slack in Sharia microfinance institutions, highlighting the potential for such behavior even within religiously guided systems.